The Impact of Innovation Engagement, Functional Engagement, Emotional Engagement, and Communal Engagement on User Loyalty in Social Media Banking Industry - Carolus Calvin Yorisco Putra Pratama; Efrata, Tommy (Universitas Dr. Soetomo, 2023)
The purpose of this study was to investigate the impact of user loyalty in social media banking on innovation engagement, functional engagement, emotional engagement, and communal engagement. With a sample of 223 banking customers who actively use social media in Indonesia, this study used survey and purposive sampling methods. Data was collected using a Google Form online questionnaire. SEM-PLS is used to process the collected data. This study tested the hypothesis that user loyalty is affected by innovation engagement, functional engagement, and emotional engagement. User loyalty is unaffected by communal engagement. As far as is known, this study is still not much research with social media objects in the banking industry compared to previous studies. The findings of this study are expected to assist Indonesian banks in determining the best strategy for increasing social media engagement in order to increase customer loyalty.